THE DEPICTION OF ISLAMIC ELEMENTS IN THE ARTWORKS OF YOUNG CONTEMPORARY AWARD - Aufa Nabila Jafri; Wan Samiati Andriana WMD, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The National Art Gallery (NAG) introduced the Young Contemporary Award (YCA), also known as Bakat Muda Sezaman (BMS), in the early 1970s with the goal of improving the creative thinking of the art scene. The platform has resulted in a significant percentage of notorious local artists producing remarkable artworks. Nevertheless, with the fast advancement of the modern era in Malaysia, the intention of presenting national culture and traditions especially the Islamic values through visual art among the Muslim artists appears to dissipate. The new generation of Muslim artists' preference for western and universal styles led to the abandonment of Islamic symbols. They appeared to ignore their own cultural motifs and ideals without concerning the impact of their decisions on the next generation of Muslim artists. Thus, this paper will discuss the examples of Islamic elements depicted in the Young Contemporary Award artworks based on the principles from the National Culture Congress 1971 using the qualitative method. It is important for these visual arts to be studied for their contribution in Islamic art. These findings can be used as source of reference to improve the content of Malaysian art making.